Survey Report on Hosts and Haustoria of Helicanthus elastica (Desr.) Danser in Udupi and Dakshina Kannada District of Karnataka and Kasaragod District of Kerala, India - A Concise Review Plus Some New Additions - Sunil Kumar, K. N.; Saraswathy, A.; Amerjothy, S. (Indian Forester, 2015)
Plants of Loranthaceae and Viscaceae are the major type of hemiparasites on aerial parts of many trees and shrubs. Mistletoes can infect taxonomically unrelated hosts and their attack has been proved to be fatal to various trees and shrubs. Plant exploration trips were conducted to different selected adjacent districts of Kerala and Karnataka to collect the plant specimens belonging to Loranthaceae. Both the host and the parasites collected were identified, mainly by using different Floras. A total of forty six plant species have been recorded as host plant for Helicanthus elastica. Out of them, twenty seven hosts were recorded in the region during this study. Out of twenty seven, fifteen host species were investigated to be new hosts for H. elastica. Coiling, knotting, coupling, creeping and the haustorial roots infecting the mother plant have been recorded. The mistletoe is found to be very common on Mangifera indica and hence recommended to be named as 'mango mistletoe'. A concise list of host records for this medicinal plant will be a ready reference for phyto-pharmaceutical academia and industry taking up the job of quality assessment of this mistletoe with reference to different host species.